n-Alkane Distributions of Modern Plants from C3-Dominated Eastern African Ecosystems - Ruth Tweedy; Caroline A E Strömberg; Tammo Reichgelt; Rahab N Kinyanjui; Mbaluka Kimeu; Venanzio Munyaka; Kevin Uno (PANGAEA, 2025)
This dataset comprises plant wax n-alkane chain length concentrations and C25-C35 relative abundances of 209 plant specimens from two Kenyan C3-dominated ecosystems, representing a wide range of plant functional types (PFTs). Plant samples were collected in 2018 from Mount Kenya National Park (n=122) and Kakamega National Forest (n=87). At Mount Kenya National Park, samples were collected along an elevational transect (~2400 m to ~3600 m above sea level) from five different ecotones: lower montane forest, bamboo zone, upper montane forest, ericaceous shrubland belt and Afroalpine moorland. Kakamega National Forest is ~1600m above sea level and samples were collected from an open glade, forest path edge, and closed canopy forest. All plant samples were identified to family level, most to genus or species level. Information on collection habitat, photosynthetic pathway, and plant functional type are included. The goal of this dataset was to assess n-alkane distributions for chemotaxonomic signals. Sample analysis took place at Lamont-Doherty Earth Observatory and Harvard University between 2022-2024. n-Alkane data were quantified using a gas chromatograph mass selective detector (GC-MSD) and a flame ionization detector (FID), and response factor corrections were calculated and applied to measured n-alkane peak areas in order to calculate corrected concentrations. The odd n-alkane C25-C35 concentrations were relativized to sum to 1 for the final relative abundance data. For more detailed information, please consult the associated manuscript on the n-alkane distributions and their chemotaxonomic significance: Tweedy et al., 2025.